RETORIKA FOTOGRAFIS PADA KARTU POS LAMA (1890-1940) YANG BERTEMA PEKERJA DI JAWA - Kusrini Kusrini (Specta: Journal of Photography, Arts, and Media, 2020)
Photographic Rhetoric On Old Postcards 1890-1940.  Photographic rhetoric is a form of visual communication in an attempt to persuade through the medium of photography. It is usually found in photo works intended for promotion. One interesting medium to review with a photographic rhetorical perspective is the old (old-fashioned) postcard. In the early 19th century, postcards became a trend everywhere including in Indonesia (Dutch East Indies, then). The function of postcards to exchange news or short messages is also carried by another purpose, namely the promotion of colonial government occupied territory. This raises a question about how to persuade through the media photos on postcards. Data collection using purposive sampling method with postcard imaginary population in the book "Workers in Java Tempo Doeloe". As for analysis using photographic rhetoric theory and visual analysis method from Gillian Rose which mentions that the interpretation of visual material can be dissected from three things, namely (1) the production of images, (2) the image itself including subject matter, and (3) the audience or consumer audience of the photo. The results showed that almost all postcard shots used long shots, as well as compositions and angles that formed distances with the audience or consumers of the photo. Attributes and properties are presented to form a "natural" and traditional feel. The gesture and expression of the worker's subject show willingness or know if it becomes the object of shooting. In addition, the indie mooi painting style is still found. The style of photo pictorialism found in some photos reinforces the mooiindie impression.  ABSTRAKKartu pos merupakan medium komunikasi berupa kartu bergambar yang dahulu dikenal sebagai carte de visite di awal kemunculannya. Tulisan ini mengkaji foto pada kartu pos lama kurun waktu 1890-1940 dengan tema pekerja tempo dulu, sebagai objek penelitian untuk mengetahui bagaimana retorika fotografisnya. Populasi foto terangkum dalam buku karya Olivier Johannes Raap berjudul “Pekerdja di Djawa Tempo Doeloe” yang terbit pada 2013. Cuplikan data menggunakan purposive sampling. Sedangkan teori retorika visual dari Gillian Rose digunakan untuk menganalisis foto-foto terpilih. Hasil kajian menunjukkan jika foto-foto di kartu pos lama menggunakan pembingkaian porsi kecil (long shot) yang menjadikan semua atribut dan properti subjek foto terlihat. Atribut dan properti dihadirkan untuk membentuk kesan alami serta tradisional, namun sekaligus memunculkan kesan jarak subjek dengan konsumen foto. Jarak pemotretan dan penataan subjek foto menciptakan ruang visual pada imaji namun juga memperkuat kesan adanya jarak sosial antara subjek foto dengan khalayaknya. Selain itu estetika fotografi masih kental dengan unsur mooi indie.